Femininity in Psychology: Basic Criteria and Approaches - Москаленко, Вікторія Василівна; Пугач, Анастасія Євгеніївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article is devoted to the main approaches to the concept of femininity in psychology. The concept of "femininity" in various areas of psychological thought was analyzed. A modern understanding of the phenomenon of femininity was described. Conceptual approaches to the concept of "femininity" are discussed. The role of mass media in shaping the image of femininity is emphasized. Representations of the female image in world culture are revealed. Female archetypes of the "emotional cold" syndrome are described in Russian folk tales. Criteria for the structure of the concept of femininity in psychology are highlighted. Many different approaches to understanding femininity are analyzed. For example, the evolutionary-biological and psychoanalytic paradigms justify femininity by Innate anatomical and physiological factors. In the theory of cognitive development, a person, in the process of self-knowledge and self-actualization, introduces himself to representatives of a certain sex. Proponents of the theory of femininity refer to the latter the following characteristics: care, benevolence in relationships, high emotional sensitivity, compliance, developed intuition, credulity, ability to negotiate with the interlocutor, the ability to compromise, the direction to maintain psychological and emotional intimacy, inconsistency, emotional speech, talkativeness, smooth movements, openness, flexibility in relationships, attentiveness to socially accepted norms, naivety, vulnerability, low self-control, taking into account the opinions of others about themselves, unstable self-esteem, demonstrativeness, tendency to self-embellish, frivolity, superficiality in judgments, impulsiveness in decision-making. A systematic holistic approach provides a model of criteria for femininity, which is convenient to represent in the form of a pyramid. It will be based on physical manifestations of femininity, inside - psychological, and at the top - spiritual. Each of these criteria is important, but it is necessary to invent an individual optimal manifestation of the physical, psychological and spiritual criteria of femininity. The media identifies three fragmentary inharmonious images of femininity (a single careerist, an unhappy housewife mother, and a sexual consumer of material goods).